Use of bovine pericardium-derived mesh in direct-to-implant reconstruction with permanent implant in the ptotic breasts (Annals of Medical Research, 2023)
Aim: Breast reconstruction is being performed more frequently in patients who have undergone mastectomy as a result of breast cancer. In this study, it was aimed to clinically investigate the efficacy and safety of the use of bovine pericardium-derived mesh in the creation of preoperative ptosis simulation in patients with grade 1-2-3 ptosis in whom skin reduction techniques are not applied and who underwent mastectomy and reconstruction with a permanent implant.Materials and Methods: Between January 2019 and April 2022, patients with grade 1, 2, and 3 breast ptosis who underwent a nipple-sparing mastectomy and simultaneous breast reconstruction with a permanent implant using bovine pericardium-derived mesh were evaluated retrospectively. Preoperative and postoperative (minimum 1 year after) anterior and oblique images of patients were evaluated. If the ptosis grade did not change in the postoperative image compared to the preoperative image, it was considered successful. If ptosis did not occur, natural breast view was not formed or the reconstruction failed, it was considered unsuccessful.Results: A total of 123 patients, 191 breasts, 55 of which were unilateral and 68 bilateral, were included in the study. The average follow-up time was 26 months. The dual plane was chosen for 130 breasts and pre pectoral plane was selected for 61 breasts. The mean age of the patients was 43.7 years. Preoperative ptosis was restored in 180 (94.2%) of 191 breasts. In five breasts with recurrent seroma formation, the bovine pericardium-derived mesh was found to be nonvascularized and was removed. No implant extrusion was observed in any of the patients during the follow-ups.Conclusion: Bovine pericardium-derived mesh is an effective and safe material in patients with ptotic breasts. In most of the patients’ breasts, bovine pericardium-derived meshes are vascularized and integrated with the tissue. Therefore, the appearance of ptosis is reestablished after surgery with bovine pericardium-derived mesh.
Keywords: Breast reconstruction; Bovine pericardium-derived mesh; Bovine pericardium; Implant-based breast reconstruction; Breast cancer